Increasing Incidence and Prevalence of World Health Organization Groups 1 to 4 Pulmonary Hypertension: A Population-Based Cohort Study in Ontario, Canada. Issue 2 (February 2018) - Wijeratne, D. Thiwanka; Lajkosz, Katherine; Brogly, Susan B.; Lougheed, M. Diane; Jiang, Li; Housin, Ahmad; Barber, David; Johnson, Ana; Doliszny, Katharine M.; Archer, Stephen L.
Abstract : Background: The World Health Organization recognizes 5 groups of pulmonary hypertension (PH), categorized by pathogenesis or comorbidity: 1-pulmonary arterial hypertension 2-left-heart disease, 3-lung disease and hypoxia 4-chronic thromboembolic disease, and 5-miscellaneous. The epidemiology of PH, apart from group 1, is largely unknown. Methods and Results: We describe incidence, prevalence, comorbidities, mortality and prescribing patterns for groups 1 to 4 PH from 1993 to 2012. Case definitions are based on hospitalizations and emergency department visits, using the Institute for Clinical Evaluative Sciences data, which comprises linked databases of universal coverage health service records for Ontario residents. This cohort included 50 529 patients with PH. The annual incidence of adult PH increased from 2003 to 2012 from 24.1 to 28.7 cases/100 000 population and the annual prevalence from 1993 to 2012 from 99.8 to 127.3 cases/100 000 population, respectively. The most common form of adult PH was group 2, alone (34.2%) or combined with group 3 PH (29.3%). A diagnosis of PH increased the 1-year standardized mortality ratio 7.2-fold. Mortality in adults with PH was 13.0%, 36.4%, and 62.4%, at 30 days, 1 year, and 5 years, respectively. Mortality was highest in groups 2 and 3 and lowest in group 1. PH was present in only 3.6% of people with left heart disease, 0.7% with lung disease, and 1.4% with thromboembolic disease, suggesting that PH is a relatively rare complication of these common diseases. Children (age<16 years) accounted for 3.6% of the cohort. In children group 1 PH was most common (65.2%), and 5-year mortality was lower (21.4%) than in adults. Group 1–specific PH therapies were increasingly prescribed over time and paradoxically were often used in patients who seemed to have group 2, PH based on diagnostic codes indicating left heart disease. Conclusions: The incidence and prevalence of adult PH are increasing. Groups 2 and 3 are the most common and lethal forms of PH. This study identifies an emerging epidemic of PH that likely has substantial adverse health and economic implications. Abstract : Supplemental Digital Content is available in the text.